Mechanoresponsive liquid crystals exhibiting reversible luminescent color changes at ambient temperature. Issue 14 (17th December 2015) - Mitani, Masato; Ogata, Shuhei; Yamane, Shogo; Yoshio, Masafumi; Hasegawa, Miki; Kato, Takashi
Abstract : Oligothiophene-based liquid crystals having a wide luminescent color variation exhibit reversible luminescent color changes induced by mechanical shearing and subsequent aging at ambient temperature. Abstract : Mechanochromic luminescent liquid crystals containing oligothiophene derivatives have been obtained. These liquid-crystalline (LC) molecules having bi-, ter-, and quarterthiophene moieties exhibit shear-induced phase transitions accompanied by changes in their luminescent colors at ambient temperature. The shear-induced LC phases and their luminescent colors spontaneously revert back to the initial LC phases and the initial luminescent colors during the thermal aging processes at ambient temperature because the shear-induced LC phases are metastable phases. These three compounds show various luminescent colors and cover a wide visible region. The terthiophene and quaterthiophene derivatives recover their initial luminescent colors faster than the bithiophene derivative, indicating that not only the luminescent colors but also the stimuli-responsive properties are tunable through simple change of the π-conjugated length of the luminescent mesogen.